Emotional Intelligence, Belongingness, and Mental Health in College Students - Moeller, Robert W.; Seehuus, Martin; Peisch, Virginia (Frontiers in Psychology, 2020)
Mental health problems are prevalent amongst today’s college students and psychosocial stress has been identified as a strong contributing factor. Conversely, research has documented that emotional intelligence (EQ) is a strong predictor of depression, anxiety and stress (mental health problems). However, the underlying mechanism whereby EQ may support stronger mental health is currently not well understood. This study used regression analyses to examine the hypothesis that belongingness (inclusion, rejection) partially mediates the effects of EQ (attention, clarity, repair) on psychological well-being in a large sample (N = 2,094) of undergraduate students. Results supported the mediation hypotheses for all three EQ components and highlighted that the effects of rejection on psychological well-being were particularly strong. In line with prior research, our results indicate that prevention and intervention efforts with college students could explicitly target EQ skills in an effort to reduce perceived rejection and promote student well-being.